2007
DOI: 10.2527/jas.2006-407
|View full text |Cite
|
Sign up to set email alerts
|

Tissue weights and body composition of two genetic lines of barrows and gilts from twenty to one hundred twenty-five kilograms of body weight1,2

Abstract: Barrows and gilts of 2 genetic lines with differing lean gain potentials (high-lean = 375 g of fat-free lean/d; low-lean = 280 g of fat-free lean/d) were used to determine tissue and organ weights and compositions from 20 to 125 kg of BW. The experiment was a 2 (genetic line) x 2 (sex) x 5 (BW) factorial arrangement of treatments in a completely randomized design conducted with 2 groups of pigs in 6 replicates (n = 120 pigs). Six pigs from each sex and genetic line were slaughtered at 20 kg of BW and at 25 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 10 publications
5
36
1
4
Order By: Relevance
“…Ganho de peso diário de suínos dos 15 aos 30kg, segundo a concentração de fósforo disponível na dieta. Apesar do padrão de resposta similar para GPD, as diferenças verificadas entre os trabalhos quanto aos níveis de Pd recomendados que proporcionaram os melhores resultados divergem entre os estudos em razão do potencial genético dos suínos para deposição de tecido muscular (Mahan, 2006;Wiseman et al, 2007 Considerando o aumento linear no CRD dos animais no presente estudo, a melhora verificada na CA permite inferir que, além do aumento no GPD até o nível de 0,450% de Pd, o aumento da concentração de Pd na dieta pode ter modificado a composição do ganho de peso, favorecendo a maior deposição muscular e a menor deposição de gordura nos animais alimentados com as dietas contendo as maiores concentrações de Pd. Segundo Stahly et al (2001), dietas deficientes em Pd, além de comprometerem o ganho de peso e a eficiência alimentar dos suínos, podem resultar em maior conteúdo de gordura corporal, influenciando de forma negativa a relação entre a deposição de proteína e de gordura na carcaça.…”
Section: Resultsunclassified
“…Ganho de peso diário de suínos dos 15 aos 30kg, segundo a concentração de fósforo disponível na dieta. Apesar do padrão de resposta similar para GPD, as diferenças verificadas entre os trabalhos quanto aos níveis de Pd recomendados que proporcionaram os melhores resultados divergem entre os estudos em razão do potencial genético dos suínos para deposição de tecido muscular (Mahan, 2006;Wiseman et al, 2007 Considerando o aumento linear no CRD dos animais no presente estudo, a melhora verificada na CA permite inferir que, além do aumento no GPD até o nível de 0,450% de Pd, o aumento da concentração de Pd na dieta pode ter modificado a composição do ganho de peso, favorecendo a maior deposição muscular e a menor deposição de gordura nos animais alimentados com as dietas contendo as maiores concentrações de Pd. Segundo Stahly et al (2001), dietas deficientes em Pd, além de comprometerem o ganho de peso e a eficiência alimentar dos suínos, podem resultar em maior conteúdo de gordura corporal, influenciando de forma negativa a relação entre a deposição de proteína e de gordura na carcaça.…”
Section: Resultsunclassified
“…This fact is probably associated, among other factors, to the possible genetic difference of animals in relation to the meat deposition potential. Assessing the total content of minerals in loin and ham of pigs from two distinct genotypes, Wiseman et al (2007) observed that the calcium and phosphorus concentrations were higher in strains with higher meat deposition potential. These results show that the phosphorus requirements may vary according to the potential of pigs for growing of lean tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The protein content of the loin and ham is sometimes slightly greater in gilts than in barrows; at other times, however, it does not differ between the two sexes (Latorre et al, 2004;Wiseman et al, 2007;Park et al, 2009a,b; Table 7). Muscular protein content usually is not affected significantly by SW within a given genotype (Unruh et al, 1996;Latorre et al, 2004); however, the protein content in the loin sometimes increases with increasing SW in lean-type pigs (Piao et al, 2004; Table 7).…”
Section: Chemical Compositionmentioning
confidence: 96%
“…Moreover, Wiseman et al (2007) and Schinckel et al (2008) have reported that muscles of a high-lean genetic line (375 gm fat-free lean gain/day) had greater growth rates and greater contents of protein and moisture, lesser daily fat gain, and lesser fat content than those of a low-lean genetic line (280 gm fat-free lean gain/day). In the studies of the present author's team, the fat content of the ham was not influenced by sex or SW (Park et al, 2009a,b), whereas the composition of fatty acids of the loin was not consistent [Lee et al, 2006;Park et al, 2007;Park et al, 2009a,b (unreported therein)].…”
Section: Chemical Compositionmentioning
confidence: 99%